Perturbation of homogeneous parabolic pseudodifferential equations by locally unbounded vector fields - Podolinnyi, S. I. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We construct solutions of homogeneous pseudodifferential equations of parabolic type perturbed by locally unbounded vector fields. We investigate some properties of these solutions.